2000
DOI: 10.2307/3871173
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Instability and Rapid Gene Silencing in Newly Formed Arabidopsis Allotetraploids

Abstract: Allopolyploid hybridization serves as a major pathway for plant evolution, but in its early stages it is associated with phenotypic and genomic instabilities that are poorly understood. We have investigated allopolyploidization between Arabidopsis thaliana (2n = 2x = 10; n, gametic chromosome number; x, haploid chromosome number) and Cardaminopsis arenosa (2n = 4x = 32). The variable phenotype of the allotetraploids could not be explained by cytological abnormalities. However, we found suppression of 20 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
218
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 134 publications
(229 citation statements)
references
References 0 publications
6
218
3
Order By: Relevance
“…(15) Indeed, transposons including DNA transposons and retrotransposons are reactivated in wheat and Arabidopsis allotetraploids. (42,61,68) In wheat, activation of Wis 2-1A retrotransposons leads to the production of readout transcripts from neighboring genes in both sense and antisense orientations. (68) Using transposon display with template cDNA, Kashkush et al (2003) found that >7% of the Wis 2-1 A-containing transcripts are novel in the amphidiploids (synonymous with allotetraploids) but absent in both parents or absent in the amphidiploids but present in one or both parents.…”
Section: Activation Of Transposons and Changes In Dna Methylation Inmentioning
confidence: 99%
See 4 more Smart Citations
“…(15) Indeed, transposons including DNA transposons and retrotransposons are reactivated in wheat and Arabidopsis allotetraploids. (42,61,68) In wheat, activation of Wis 2-1A retrotransposons leads to the production of readout transcripts from neighboring genes in both sense and antisense orientations. (68) Using transposon display with template cDNA, Kashkush et al (2003) found that >7% of the Wis 2-1 A-containing transcripts are novel in the amphidiploids (synonymous with allotetraploids) but absent in both parents or absent in the amphidiploids but present in one or both parents.…”
Section: Activation Of Transposons and Changes In Dna Methylation Inmentioning
confidence: 99%
“…(21) How are orthologous protein-coding genes regulated in synthetic interspecific hybrids and allotetraploids? To address this question, several groups took AFLP-cDNA display approaches to uncover novel gene expression patterns in synthetic Arabidopsis allotetraploids and natural A. seucica, (42,70) cotton (31) and wheat (68,82) allotetraploids. Synthetic Arabidopsis allotetraploids were produced by direct hybridization between an A. thaliana Ler autotetraploid and A. arenosa, a naturally outcrossing tetraploid.…”
Section: Activation Of Transposons and Changes In Dna Methylation Inmentioning
confidence: 99%
See 3 more Smart Citations